Peranan Good Corporate Governance Memoderasi Hubungan Agency Cost, Enterprise Resource Planning dan Growth Opportunity Terhadap Kinerja Perusahaan - Hadiyanti, Sylvia Dwi; Sugiyanto, Sugiyanto (Journal of Management Accounting, Tax and Production, 2024)
This study aims to determine the role of Good Corporate Governance in moderating the relationship between Agency Cost, Enterprise Resource Planning and Growth Opportunity on Company Performance (Study on Financial Sector Companies listed on the Indonesia Stock Exchange for the 2018-2022 Period). This type of research uses quantitative. The sample in this study was obtained using Purposive Sampling, so that 22 (twenty two) companies were obtained with a research period of 2018-2022 so that 110 (one hundred and ten) sample units were obtained. The methodology used is using the chow test, hausman test, and multiple langrange test for model selection. As well as descriptive statistical tests, classical assumption tests, panel data regression analysis tests and Moderated Regression Analysis (MRA). The data used are secondary data. The analysis method used is a hypothesis with the help of E-Views 12. The results of this study are that based on a partial test, agency costs do not affect company performance, enterprise resource planning affects company performance and growth opportunities do not affect company performance. Based on the moderation test, good corporate governance strengthens the relationship between agency costs and company performance, good corporate governance strengthens the relationship between enterprise resource planning and company performance and good corporate governance weakens the relationship between growth opportunities and company performance.